2005
DOI: 10.1111/j.0105-2896.2005.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of aged mice to primary virus infections

Abstract: Aging is associated with an increased morbidity to virus infections as well as a delay in clearance of symptoms after infection. Studies of sublethal virus infections of aged mice closely mirror the human situation: there is a delay in clearance of virus. The delay in virus clearance is accompanied by a delay and a decrease in T-cell response, particularly of CD8(+) T cells. Intrinsic alterations of T cells of aged mice contribute to this decrease in virus-specific T-cell response; however, evidence suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 55 publications
(69 reference statements)
6
59
0
Order By: Relevance
“…Indeed, and in line with a previous report (47), we observed transiently reduced YF-neutralizing Ab titers in elderly vaccinees, which could probably be attributed to the delayed production of YF-specific IgM Abs (data not shown). In addition, YF-specific CD8 + T cells, known to complement humoral anti-YF immunity (35), were clearly reduced in numbers and in the acute phase of the response in the aged cohort, confirming similar observations from various aged animal models (49,(51)(52)(53). Although we could demonstrate an age-related proliferative defect of these cells in the acute phase as it has been seen also in aged mice after Listeria monocytogenes infection (54), other functional properties such as the specific CD8 + cytotoxicity and cytokine expression remain to be addressed by future studies.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, and in line with a previous report (47), we observed transiently reduced YF-neutralizing Ab titers in elderly vaccinees, which could probably be attributed to the delayed production of YF-specific IgM Abs (data not shown). In addition, YF-specific CD8 + T cells, known to complement humoral anti-YF immunity (35), were clearly reduced in numbers and in the acute phase of the response in the aged cohort, confirming similar observations from various aged animal models (49,(51)(52)(53). Although we could demonstrate an age-related proliferative defect of these cells in the acute phase as it has been seen also in aged mice after Listeria monocytogenes infection (54), other functional properties such as the specific CD8 + cytotoxicity and cytokine expression remain to be addressed by future studies.…”
Section: Discussionsupporting
confidence: 78%
“…ging is accompanied by a decline in immune function (1,2). That decline is believed to be the most important contributing factor to the known susceptibility of older adults to various infections and to their often suboptimal response to vaccination (3,4).…”
mentioning
confidence: 99%
“…Although some studies reported that CD8 T cell responses are negatively affected in older animals both in vitro (31,32) and in vivo (33)(34)(35) or that T cell repertoire diversity and effector functions are altered (19,36,37), other data suggest that aged CD8 T cells are not intrinsically defective (38,39). In response to viral infection, CD8 T cell responses have been assessed quantitatively (33,36), and, although numerical decreases have been reported (37), it remains unclear if there are also qualitative differences between antiviral CD8 T cells from young or aged mice.…”
mentioning
confidence: 99%